Clinical pharmacokinetics of oral levofloxacin and sitafloxacin in epididymal tissue. Issue 4 (April 2017) - Sadahira, Takuya; Wada, Koichiro; Ikawa, Kazuro; Morikawa, Norifumi; Kurahashi, Hiroaki; Yoshioka, Takashi; Ariyoshi, Yuichi; Kobayashi, Yasuyuki; Araki, Motoo; Ishii, Ayano; Watanabe, Masami; Uehara, Shinya; et al.
Abstract: Objectives: This study aimed to investigate the penetration of fluoroquinolones into human epididymal tissue. Methods: The penetration of levofloxacin (LVFX) 500 mg or sitafloxacin (STFX) 100 mg into epididymal tissue was examined. Patients with prostate cancer who were referred for orchiectomy were included. LVFX 500 mg (n = 9) or STFX 100 mg (n = 9) was administered orally 1 h before orchiectomy, and 0.5 g of epididymal tissue and blood samples were collected simultaneously during surgery. Drug concentrations were measured by high-performance liquid chromatography, and patient characteristics and adverse events were analyzed. Results: The mean ratio of the epididymal concentration to the serum concentration was 1.48 ± 0.45 for LVFX and 1.54 ± 0.81 for STFX. For LVFX, the simulated curves estimated the following: maximum concentrations (Cmax) of 8.84 μg/ml in serum and 14.1 μg/g in epididymal tissue and area under the concentration-time curve for 24 h (AUC24 ) of 68.5 μg h/ml in serum and 108.9 μg h/g in epididymal tissue. For STFX, the Cmax was 1.22 μg/ml in serum and 1.66 μg/g in epididymal tissue, and the AUC24 was 9.58 μg h/ml in serum and 13.1 μg h/g in epididymal tissue. Neither treatment-related adverse events nor postoperative urogenital infections were observed. Conclusions: The results of this study suggest that oral administration of LVFX 500 mg or STFX 100 mg achieves effective epididymal concentrations for treatment of epididymitis.